Studies on the Lipolytic Enzymes of Sesamum indicum Seed Powder: Lipolytic Enzymes of Sesamum indicum - Rahman, Salma; Akhtar, Nusrullah; Jabbar, Abdul (Biological Sciences - PJSIR, 2009)
Optimum conditions for the hydrolysis of simple triglycerides and phosphoglycerides for the activity of the lipolytic enzymes (lipase and phospholipase) extracted from the defatted seeds of Sesamum indicum were established for use in laboratory and industry. The enzymes showed optimum activity at 40 °C and pH 7 in aqueous media. N-heptane was found to be the most satisfactory solvent for maximum activities. The activity of lipase extracted from germinated seeds increased with the stage of seed development, but was reverse for the phospholipase activity.